Current Trends in Population Protection in Europe and Their Research Support in the Czech Republic - Linhart, Petr (Communications - Scientific letters of the University of Zilina, 2005)
In the contribution, on the base of a systematic study of evolution trends in the field of population protection in some European countries, current looks on a wide-spectral approach of this issue were generalized. The contribution deals with: Protection of population as an integrated system, Risks and threats, Mission, Main tasks, Powers, Rescue entities, Management structures, Service model, Education and training, Protective infrastructure, and International co-operation. In connection with the necessity of research support of measures for population protection, the current state in this issue in the Czech Republic was described.